Epidemiologic Spatial Analysis of a Tuberculosis Incidence in Bandung City in 2021 - Rosady, Dony Septriana; Zulfa, Nysa Ro Aina; Pratama, Sony Bagja (Global Medical & Health Communication (GMHC), 2024)
Tuberculosis (TB) is a communicable disease that is a significant cause of ill health and one of the leading causes of death worldwide. Tuberculosis remains a major global health problem. Tuberculosis infection remains one of the biggest health problems in Indonesia, which ranked second in the world on the list of countries with a high burden of TB. This is a cross-sectional study where the research displays population data, population density, and the incidence of TB in Bandung city, which is visualized in the mapping. This research analyzed the relationship between population density and the incidence of TB. The area with the highest TB incidence was the Babakan Ciparay subdistrict, with a total of 469 people and a population density of 205 people/hectare. The study has shown a strong relationship and a positive correlation between population density and the incidence of TB in Bandung city (p<0.001, r=0.603). Tuberculosis cases tend to be higher in areas with high population densities. Besides population density, other factors influence the incidence of TB in an area. House technical factors such as adequacy of windows, air ventilation, and lighting influence TB transmission. Besides that, household sanitation factors and occupancy density also impact the incidence of TB. In conclusion, subdistricts with a high population density show a high incidence of TB. There is a strong and unidirectional relationship between population density and the incidence of TB.